Pinnularia wuyiensis sp. nov., a new diatom (Bacillariophyceae, Naviculales) from the north region of Wuyi Mountains, Jiangxi Province, China - Zahng, Wei; Pereira, Andreia Cavalcante; Kociolek, J. Patrick; Liu, Caihong; Xu, Xiaoying; Wang, Liqing (Phytotaxa, 2016)
One new species of the genus Pinnularia is described, Pinnularia wuyiensis sp. nov., from the Xinjiang River, Yingtan City, in the northern region of Wuyi Mountains, Southeast China. This new taxon is characterized by a narrowly linear-lanceolate valve, with slightly undulate margins and a gibbous center and rounded, capitate and broadly rounded apices, a very narrow axial area, and a central area generally forming asymmetric, rhombic fascia. The species is compared to Pinnularia gibbiformis, P. gibba, P. polyonca, P. polyonca var. stidolphii, P. polyonca var. sumatrana, P. amazonica and P. subboyeri, all of which closely resemble Pinnularia wuyiensis but differ from the new species in specific details of size, striae density and valve shape. In addition, the ecology of this new species is also described in this paper.